O10-4 Ionizing radiation exposure and risks of cancer and circulatory disease in technologists performing nuclear medicine procedures. (1st September 2016) - Kitahara, Cari; Doody, Michele; Dyke, Miriam Van; Drozdovitch, Vladimir; Simon, Steven; Lim, Hyeyeun; Preston, Dale; Miller, Jeremy; Brill, Aaron; Bolus, Norman; Little, Mark; Freedman, D Michal; et al.
Abstract : The number of nuclear medicine procedures performed has increased substantially over the past several decades, resulting in potentially greater radiation exposure to the technologists who perform them. However, there have been no epidemiologic studies of cancer or other serious health effects in these workers. Using data from the U.S. Radiologic Technologists (USRT) Study (1994–1998), we prospectively examined risks of cancer and circulatory disease (incidence through 2005 and mortality through 2008) associated with reported performance of nuclear medicine and brachytherapy procedures. Although risks for most outcomes examined were not elevated, we observed increased risks for squamous cell carcinoma of the skin (HR = 1.29, 95% CI: 1.01–1.66) with ever performing diagnostic radionuclide procedures, for myocardial infarction incidence (HR = 1.37, 95% CI: 1.10–1.70), all-cause mortality (HR = 1.10, 95% CI: 1.00–1.20) and all-cancer mortality (HR = 1.20, 95% CI: 1.01–1.43) with ever performing brachytherapy; also mortality from all causes (HR = 1.14, 95% CI: 1.01–1.30), breast cancer (HR = 2.68, 95% CI: 1.10–6.51), and myocardial infarction (HR = 1.76, 95% CI: 1.02–3.04) were associated with ever performing other radionuclide therapy procedures; higher risks were also observed with greater frequency of performing these procedures before 1980. For a sample of 4, 406 technologists in USRT who completed a detailed work history survey in 2013–14, we described trends over the past six decades in nuclear medicine work history practices. We found that the frequency of most diagnostic nuclear medicine procedures performed by technologists increased over time, particularly for cardiac and positron emission tomography (PET) scans, while the frequency of therapeutic procedures performed remained stable. Although adherence to most radiation protection practices increased, lead apron use sharply declined. Estimation of organ-specific occupational radiation doses for individual technologists using these data (in progress) will be used in comprehensive retrospective and prospective investigations of radiogenic cancer and other serious disease risks. A study evaluating nuclear medicine work history practices and associated doses in a sample of U.S. technologists who are more recently trained and primarily certified in nuclear medicine technology is currently underway.